2008
DOI: 10.1007/s10584-007-9382-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating regional climate model estimates against site-specific observed data in the UK

Abstract: This paper compares precipitation, maximum and minimum air temperature and solar radiation estimates from the Hadley Centre's HadRM3 regional climate model (RCM), (50×50 km grid cells), with observed data from 15 meteorological station in the UK, for the period 1960-90. The aim was to investigate how well the HadRM3 is able to represent weather characteristics for a historical period (hindcast) for which validation data exist. The rationale was to determine if the HadRM3 data contain systematic errors and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Rivington et al, 2008;Themessl et al, 2012) and, more importantly, that this degrades Figure 9, but for the projected changes over the winter months (December-February). This figure is available in colour online at wileyonlinelibrary.com/journal/qj further when quantifying extreme rainfall events that are the cause of floods -the interest of this paper.…”
Section: To Mos or Not To Mosmentioning
confidence: 92%
“…Rivington et al, 2008;Themessl et al, 2012) and, more importantly, that this degrades Figure 9, but for the projected changes over the winter months (December-February). This figure is available in colour online at wileyonlinelibrary.com/journal/qj further when quantifying extreme rainfall events that are the cause of floods -the interest of this paper.…”
Section: To Mos or Not To Mosmentioning
confidence: 92%
“…However, because actual topographic and geographic features may vary within model grid boxes, a direct comparison of model output with observations may be beyond a regional model's design (Rivington et al 2008). Nevertheless, to gain insight into the potential of RegCM to simulate significant and extreme temperature and precipitation events on small scales, we first compared model climatology for the reference period with data from 20 selected stations in Croatia (Fig.…”
Section: Simulation and Effects Of Climate Change On Local Significanmentioning
confidence: 99%
“…However, it has been widely recognized that the GCMs were not designed to make projections at a regional scale (Carbone et al 2003, Christensen et al 2007, while the spatial resolution of RCMs such as the RegCM2 at 50 × 50 km is more appropriate . Mearns et al (2003) examined the performance of the GCMs and RCMs by comparing their present-day projections with global or regional scale aggregations of observed weather data (Rivington et al 2008). They found that the CSIRO and RegCM2 models generated different projections for the southeastern USA.…”
Section: Introductionmentioning
confidence: 99%